Phytochemical Investigation of Medicinal Plants Cinicus wallichii and Cnicus benedictus L. - Kataria, H.C. (Asian Journal of Chemistry, 2010)
In the present work, the phytochemical studies of Cnicus wallichii and Cinicus benedictus L. have been studied.